2017
DOI: 10.1523/eneuro.0034-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Early Social Isolation Stress and Perinatal NMDA Receptor Antagonist Treatment Induce Changes in the Structure and Neurochemistry of Inhibitory Neurons of the Adult Amygdala and Prefrontal Cortex

Abstract: The exposure to aversive experiences during early life influences brain development and leads to altered behavior. Moreover, the combination of these experiences with subtle alterations in neurodevelopment may contribute to the emergence of psychiatric disorders, such as schizophrenia. Recent hypotheses suggest that imbalances between excitatory and inhibitory (E/I) neurotransmission, especially in the prefrontal cortex and the amygdala, may underlie their etiopathology. In order to understand better the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 84 publications
(118 reference statements)
15
82
0
Order By: Relevance
“…Human postmortem studies revealed marked abnormalities of aggrecan and PV-expressing neurons in schizophrenia and bipolar disorder (Pantazopoulos et al, 2015;Steullet et al, 2018). Preclinical studies also showed that early life stress or chronic stress during adulthood altered PNN numbers in multiple brain regions including prefrontal cortex (Castillo-Gómez et al, 2017;de Araújo Costa Folha et al, 2017;Pesarico et al, 2019). The PNN assembly and its molecular components may play a critical role in stress response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human postmortem studies revealed marked abnormalities of aggrecan and PV-expressing neurons in schizophrenia and bipolar disorder (Pantazopoulos et al, 2015;Steullet et al, 2018). Preclinical studies also showed that early life stress or chronic stress during adulthood altered PNN numbers in multiple brain regions including prefrontal cortex (Castillo-Gómez et al, 2017;de Araújo Costa Folha et al, 2017;Pesarico et al, 2019). The PNN assembly and its molecular components may play a critical role in stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated the alterations in the density or composition of PNNs in a range of neuropsychiatric disorders such as epilepsy (Tewari et al, 2018), schizophrenia (Bitanihirwe and Woo, 2014;Enwright et al, 2016), bipolar disorder (Steullet et al, 2018), and drug addiction (Xue et al, 2014;Blacktop and Sorg, 2019), and these behavioral abnormalities might be improved after reversing the changes in the number of components of PNNs. Chronic stress during early life or adulthood alters the density of PNNs in the medial prefrontal cortex, and affects the structure and plasticity of inhibitory neurons, especially PV-expressing interneurons (Castillo-Gómez et al, 2017;de Araújo Costa Folha et al, 2017;Pesarico et al, 2019). Early life maltreatment or maternal immune activation caused developmental abnormalities in PNNs in the prefrontal cortex and basolateral amygdala (Paylor et al, 2016;Page and Coutellier, 2018;Santiago et al, 2018), which may be associated with the increased vulnerability to neuropsychiatric disorders such as anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors regulate the formation and maintenance of both the dendritic tree and the density of dendritic spines. Among those are neurotrophins, such as BDNF, neurotransmitters, such as glutamate, molecules, such as nitric oxide and even some hormones, such as glucocorticoids (Castillo‐Gómez et al, ; Flores, Morales‐Medina, & Diaz, ; Gilabert‐Juan et al, ; Pérez‐Rando et al, ). Interestingly, stress may modify these factors (for review see McEwen, ; Duman & Duman, ; Bennett & Lagopoulos, ; Flores, Flores‐Gómez, & Gómez‐Villalobos, ; Flores, Morales‐Medina, & Diaz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mice that were socially isolated two weeks after weaning displayed cognitive and behavioral dysfunction that was associated with alterations in the white matter tracts of the prefrontal cortex [19]. Adolescent social isolation also lead to more immature dendritic spines, impaired plasticity in the prefrontal cortex [21], and altered the morphology of inhibitory circuits in the prefrontal cortex and basolateral amygdala [22]. Similar effects of social isolation can also be induced using much longer periods of single housing in adulthood, with adult mice showing that prolonged social isolation-induced behavioral, transcriptional and ultrastructural changes in oligodendrocytes in the prefrontal cortex, resulting in impaired myelination [23].…”
Section: Introductionmentioning
confidence: 99%